Broken vessels : the im-possibility of the art of remembrance and re-collection in the work of Anselm Kiefer, Christian Boltanski, William Kentridge and Santu Mofokeng - Belluigi, Dina Zoe (Rhodes University, Faculty of Humanities, Department of Fine Art, 2002)
This thesis is structured around investigating the philosophical and aesthetic problematics, politics, and possibilities of representing the past for the purposes of demythifying the present as well as commemorating the losses of history, as explored in the artworks of Anselm Kiefer, Christian Boltanski, William Kentridge and Santu Mofokeng. The first chapter begins with Theodor Adorno's philosophical understanding of myth and history: how he is influenced by and then develops Karl Marx's critique of society, Sigmund Freud's critique of reason and its subject, and particularly Walter Benjamin's ideas of history as catastrophe, the role of the historian and his messianic materialism. The second section looks at Theodor Adorno's dialectic of art and society: immanent criticism in aesthetic practice, mimesis, and the shift in conceptions of allegory from Walter Benjamin's understanding to that of Jacques Derrida. The last section of the chapter looks at Jacques Derrida's poststructuralist theories against boundary-fixing, within that the ethical relation to the 'other' and the theorist/artist as psychic exile. The second chapter deals with the politics of remembrance and representation "” beginning with Theodor Adorno's historic interpretation of the Mosaic law against the making of images and Jean-Francois Lyotard on the im-possibility of representing the unrepresentable. The chapter is divided in two parts between the post-Holocaust European artists Anselm Kiefer and Christian Boltanski, and the post-apartheid South African artists William Kentridge and Santu Mofokeng. It explores, within these artists' specific contexts, their formal and philosophical approaches to myth and history, and the problematics of image-making, representing the unrepresentable, and commemorating the immemorial. The thesis concludes by considering different conceptions of melancholia as they relate to these artists: the Freudian psychoanalytic approach, Benjamin's notions of the artist-genius, and Julia Kristeva's Lacanian reading of the humanist melancholic, concluding with the mythic-historical Kaballist notion of melancholia as the historical burden or responsibility to commemorate loss.
Keywords: History in art; Kiefer, Anselm, 1945-; Boltanski, Christian, 1944-; Kentridge, William, 1955-; Mofokeng, Santu, 1956-